Efecto de la nutrición orgánica en el cultivo de zucchini cucurbita pepo l. var. black beauty, sector Moraspamba-la Argelia 2014 - Saritama Torres, María del Cisne (2014)
This research project is entitled "Effect of Organic Crop Nutrition in Cucurbita pepo Zucchini l Var. Black Beauty, Moraspamba-Algeria 2014 "sector, in order to give a contribution of field research, the following objectives:  Evaluate the agronomic performance of growing zucchini over the application of four organic manures. Humus, Compost, Manure fosfoestiércol and goat sector in Algeria Moraspamba- The  Evaluate the physical, chemical Moraspamba- The soil of Algeria sector before planting and after harvest analysis.  Determine the cost of production and profitability of growing zucchini for each treatment.  Disseminate research results. Statistical randomized block design was used with five treatments and four replications, treatments used for the study were: Compost, fumes, fosfoestiércol, goat manure and absolute control, in order to improve the physical and chemical properties of soil by providing organic fertilizer to increase crop yield Zucchini. To evaluate the performance of Zucchini growing in each treatment was determined: percentage of germination percentage of surviving, growth rates, days to physiological maturity and harvest, number of fruits per plant, fruit weight and yield per plot in kilograms - kg-ha plot. The germination percentage on the fifteenth day of germination was higher T3 (Fosfoestiércol) treatments with 98.75%, followed by T4 (goat manure) and treatment was 98.13% respectively. Treatments were presented taller 31.70 cm fosfoestiércol treatment and 30.23cm goat manure and regarding the variable days harvest physiological maturation and no significant difference between treatments are between 100 days, also with days to harvest because the treatment has fewer days is the witness and compost. To evaluate the improvement of soil properties, analysis of the four organic fertilizers was conducted, as well as the end of culture in each treatment. Analyses were performed in the laboratory of the National University of Loja. For the yield per hectare, the productivity per hectare had statistical significance between treatment versus control was determined, with better performance goat manure treatment with 172, 91 t / ha, the treatment fosfoestiércol 165.34 t / ha, the smoke of 156.30 t / ha compost 147.61 t / ha compared to the control that had an output of 115.74 t / ha. The highest performance in growing Zucchini was obtained in the treatment of goat manure, relating to the results of the laboratory in which that this treatment increased further the content of soil organic matter of 1.235 to 3 is observed, 78%, the content of fosfoestiércol of. By obtaining results hummus was the most profitable organic fertilizer with respect to production costs with a cost benefit ratio of $ 1.37 versus $ 1.18 goat manure, this due to the humus requires few materials for its preparation that through this research will be able to take corrective action.